Chapter 11 National Theatres in Africa Between Modular Modernity and Cultural Heritage - Balme, Christopher B. (Taylor & Francis, 2024)
In sub-Saharan Africa a number of national theatres were established from the 1950s onwards. Their construction involved British colonial administration, American philanthropy and Chinese development aid. While each history is particular, they share certain common experiences that can be read as an allegory of postcolonial history. This narrative is bracketed by the seemingly contradictory terms modular modernity and cultural heritage: modernity with its promise of the new, cultural heritage with its ideology of preservation. While apparently oppositional terms, they are in fact two points on a continuum of Western and Asian influence on the African continent. There is a direct through-line connecting modular modernity with cultural heritage discourse of the post-Cold War period. This chapter's main example is the National Theatre in Uganda which can read as a test case of shifting discourses and agendas in the context of the Cultural Cold War and its long-term implications.